A Product Analysis and Growth Strategy Proposal for Kaleido - Sagols, Michael; Andera, Michal, 1984-; Ulrich-Diener, Florian; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This master’s thesis explores the integration of Virtual Reality (VR) technology to improve caretaker onboarding processes in retirement homes, focusing on a company named Kaleido. The goals were to assess the feasibility, market potential, and strategic impact of VR in enhancing the quality of life for the elderly. The methodology employed a quantitative approach, revealing significant potential for VR to reduce caretaker turnover by streamlining training and enhancing care quality. The thesis concludes that implementing VR could significantly enhance operational efficiency and care quality in retirement homes, particularly in the Czech Republic and Germany, and recommends further development of VR training modules tailored to caretaker needs. The study effectively integrates theory with practical application, offering a robust framework for leveraging VR technology in elderly care.
Vedoucí práce: Michal Andera
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses